The knowledge of nurses about the delivery plan - Amanda Peres Zubiaurre de Barros; Jussara Mendes Lipinski; Graciela Dutra Sehnem; Alessandra Nunes Rodrigues; Eriane da Silva Zambiazi (Universidade Federal de Santa Maria, 2017)
Aim: To identify the knowledge of nurses from a municipality on the western border of Rio Grande do Sul about the birth plan (PP). Method: Qualitative, descriptive and exploratory research, developed with 15 nurses who attended prenatal care in Family Health Strategies (FHS). Data collection took place in April and May 2016. Using a semistructured instrument, the analysis was of content in the thematic modality. Results: Three categories emerged: Birth Plan, what is it?, which addresses the nurses' lack of knowledge about PP; The need for training for professional practice, which presents the interest of nurses in training; Possibilities and limitations for PP implementation, in which the nurses report easinesses and weaknesses in view of delivery attention in the municipality. Final considerations: The study allowed a deepening of the thematic, providing reflections to professionals who were included in Primary Health Care.